2014
DOI: 10.1177/1098611114549629
|View full text |Cite
|
Sign up to set email alerts
|

Policing “The Patch”: Police Response to Rapid Population Growth in Oil Boomtowns in Western North Dakota

Abstract: This study examines police response to rapid population growth resulting from the oil boom in western North Dakota. This study uses methodological triangulation to examine how rapid population growth has affected the way that police personnel conduct their work and interact with citizens in their communities. Data sources include face-to-face interviews with 101 sworn police personnel working in eight agencies, across four counties in western North Dakota, and examination of official data (including concealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 8 publications
2
23
0
1
Order By: Relevance
“…Though this early scholarship was critiqued for its ad hoc arguments and methodological limitations (Wilkinson et al 1982(Wilkinson et al , 1984, it helped lay the groundwork for more sophisticated research, still largely rural in focus. Extractive booms have been connected to increased crime (Archbold, Dahle, and Jordan 2014;Komarek 2016;Ruddell et al 2014), strain on infrastructure (Goodman et al 2016;Graham et al 2015;Rahm, Fields, and Farmer 2015), and more general quality-of-life impacts (Fernando and Cooley 2015)-all of which could reduce the economic vitality of a community. Still, boomtown development typically occurs in distinct phases, and some communities can adapt to and recover from the strains and social disruptions of resource booms and busts-even while others do not (Brown, Dorius, and Krannich 2005;Freudenburg 1981;Smith, Krannich, and Hunter 2001).…”
Section: Boomtownsmentioning
confidence: 99%
“…Though this early scholarship was critiqued for its ad hoc arguments and methodological limitations (Wilkinson et al 1982(Wilkinson et al , 1984, it helped lay the groundwork for more sophisticated research, still largely rural in focus. Extractive booms have been connected to increased crime (Archbold, Dahle, and Jordan 2014;Komarek 2016;Ruddell et al 2014), strain on infrastructure (Goodman et al 2016;Graham et al 2015;Rahm, Fields, and Farmer 2015), and more general quality-of-life impacts (Fernando and Cooley 2015)-all of which could reduce the economic vitality of a community. Still, boomtown development typically occurs in distinct phases, and some communities can adapt to and recover from the strains and social disruptions of resource booms and busts-even while others do not (Brown, Dorius, and Krannich 2005;Freudenburg 1981;Smith, Krannich, and Hunter 2001).…”
Section: Boomtownsmentioning
confidence: 99%
“…Second, research indicates oil and gas development does increase crime (Archbold, Dahle, & Jordan, 2014;Carrington et al, 2012;James & Smith, 2017;Martin et al, 2019;Ruddell, 2011;Ruddell, Jayasundara, Mayzer, & Heitkamp, 2014;, with police services stretched increasingly thin and given little or no additional resources to address new crime issues (Archbold, Dahle, & Jordan, 2014;James & Smith, 2017;Ruddell, 2011). The lack of UCR or NIBRS data in these rural locations makes longitudinal trends difficult to determine (James & Smith, 2017; while booms on tribal land suffer from even less official crime data as tribal crime data are only sporadically reported to the FBI (Indian Law & Order Commission, 2013).…”
Section: Crime and Perceptions Of Crime In Oil And Gas Boomtownsmentioning
confidence: 99%
“…Overall, boomtowns tend to experience an increase in the volume of calls for service by police (Archbold et al, 2014;James & Smith, 2017;Ruddell, 2011;. Research shows boomtowns experienced an increase in all crime categories except burglary (James & Smith, 2017), but a small increase in: violent crimes (e.g., rape, robbery, and murder), aggravated assault, and grand auto theft (James & Smith, 2017;Martin et al, 2019); violent and property crime (Martin et al, 2019;; domestic violence (Archbold et al, 2014;Martin et al, 2019), as well as alcohol intoxication and traffic-related offenses (Archbold et al, 2014). In their examination of crime data in the Bakken oil-producing region, Martin et al (2019) found that that violent victimization (e.g., murder, rape, sexual assault, unlawful sexual contact, robbery, assault, kidnapping, and intimidation) rate rose by 31 percent for men and 18 percent for women between 2006 and 2012.…”
Section: Crime and Perceptions Of Crime In Oil And Gas Boomtownsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only did the size of small and rural communities increase, but the composition of the newcomer population-predominantly made up of young, high-salaried males with little stake in the community-leads to increased involvement in antisocial behaviour and crime (Dahle & Archbold, 2015). Police officers reported many of these newcomers had prior criminal records (Archbold, Dahle, & Jordan, 2014), and researchers found that the proportion of registered sex offenders living in resource-based boom communities was higher than in neighbouring jurisdictions (Berger & Beckman, 2010;Jayasundara, Heitkamp, Mayzer et al, 2016a).…”
mentioning
confidence: 99%